Monetary Policy Impact on Household Welfare Through Consumption in Nigeria - Joel, Olaoye, Oyebanji; Anyanwu, Sarah O.; Richard, Umeokwobi, Onyekachi, (Journal of Ecohumanism, 2025)
This research investigates the relationship between monetary policy and welfare, utilizing household consumption expenditure as an indicator of welfare. The analysis covers the period from 2000 to 2023, employing monthly data. The study reached several key conclusions by applying the Structural Vector Autoregressive (SVAR) model, a variant of the unrestricted VAR model designed for forecasting multiple interrelated variables. It was found that while the interbank rate, M2, and exchange rate exhibit significant independence, household consumption expenditure is highly sensitive to monetary conditions. The overwhelming impact of M2 on household expenditure, which accounts for nearly 96.0 percent of its variance by the conclusion of the forecast period, highlights the critical importance of money supply in shaping consumption behaviors. This outcome indicates that monetary policy, especially through money supply mechanisms, wields considerable influence over household spending choices.